Anti-bacterial effects of components from Sanguisorba officinalis L. on Vibrio vulnificus and their soluble epoxide hydrolase inhibitory activity - Xiang Dong Su; Rui Hong Guo; Seo Young Yang; Young Ho Kim; Young Ran Kim (Natural Product Research, 2019)

Individual exposure to particulate matter in urban and rural Chinese households: estimation of exposure concentrations in indoor and outdoor environments - Minna Guo; Rui Xing; Yoko Shimada; Gakuji Kurata (Natural Hazards, 2019)

The T cell activating properties and antitumour activity of Staphylococcal Enterotoxin-like Q - Yanan He; Yuliang Sun; Yakun Ren; Liang Qiao; Rui Guo; Jiang Du; Xinxing Zhu; Yanli Liu; Juntang Lin (Medical Microbiology and Immunology, 2019)

Molecular mapping of the gene(s) conferring resistance to Soybean mosaic virus and Bean common mosaic virus in the soybean cultivar Raiden - Mian Wu; Ying-Na Liu; Cong Zhang; Xue-Ting Liu; Cheng-Chen Liu; Rui Guo; Ke-Xin Niu; An-Qi Zhu; Jia-Yin Yang; Jian-Qun Chen; Bin Wang (Theoretical and Applied Genetics, 2019)

The basolateral amygdala regulation of complex cognitive behaviours in the five-choice serial reaction time task - Fangyuan Yin; Hao Guo; Jingjing Cui; Yuhui Shi; Rui Su; Qiaoli Xie; Jinrui Chang; Yunpeng Wang; Jianghua Lai (Psychopharmacology, 2019)

Urbanization and CO2 emissions in resource-exhausted cities: evidence from Xuzhou city, China - Shanshan Guo; Yanfang Zhang; Xiangyan Qian; Zhang Ming; Rui Nie (Natural Hazards, 2019)

Filler improvement and purification effects of constructed rapid infiltration facility - Rui-song Zhao; Jia-ke Li; Chao Guo; Fan Li; Huai-en Li (Environmental Science and Pollution Research, 2019)

The Functional Analysis of Selenium-Related Genes and Magnesium-Related Genes in the Gene Expression Profile Microarray in the Peripheral Blood Mononuclear Cells of Keshan Disease - Sen Wang; Rui Yan; Bin Wang; Peiling Meng; Wuhong Tan; Xiong Guo (Biological Trace Element Research, 2019)

Design and Experiment of a Plateau Data-Gathering AUV - Hao Xu; Guo-Cheng Zhang; Yu-Shan Sun; Shuo Pang; Xiang-Rui Ran; Xiang-Bin Wang (Journal of Marine Science and Engineering, 2019)
The design, control, and implementation of an autonomous underwater vehicle (AUV) for collecting hydrological information from plateau rivers and lakes are presented in this paper. The hardware and software structures of the control system were previously described. A novel sliding mode controller (SMC) with combinational reaching law of vertical hovering motion is proposed to improve the robustness and stability. The S-plane control, a nonlinear controller with little parameters, is used in the horizontal motion. Besides, the navigation strategy based on the dead-reckoning algorithm, a path tracking based on the light-of-sight (LOS) algorithm, and a control allocation strategy considering saturation are present. Finally, experiments were performed in a tank and in a river in the Qinghai–Tibet Plateau to prove the feasibility and reliability of the AUV system.

Integrated analysis of miRNAs and their targets reveals that miR319c/TCP2 regulates apical bud burst in tea plant (Camellia sinensis) - Shengrui Liu; Xiaozeng Mi; Ran Zhang; Yanlin An; Qiying Zhou; Tianyuan Yang; Xiaobo Xia; Rui Guo; Xuewen Wang; Chaoling Wei (Planta, 2019)

The faster-onset antidepressant effects of hypidone hydrochloride (YL-0919) - Li-jun Sun; Li-ming Zhang; Dan Liu; Rui Xue; Yan-qin Liu; Lei Li; Ying Guo; Chao Shang; Jun-qi Yao; You-zhi Zhang; Yun-feng Li (Metabolic Brain Disease, 2019)

Bivariate copula function-based spatial–temporal characteristics analysis of drought in Anhui Province, China - Rui Wang; Chunli Zhao; Jiquan Zhang; Enliang Guo; Danjun Li; Si Alu; Si Ha; Zhenhua Dong (Meteorology and Atmospheric Physics, 2019)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

De Novo Assembled Transcriptome Analysis and Identification of Genic SSR Markers in Red-Flowered Strawberry - Yan Ding; Li Xue; Rui-xue Guo; Gang-jun Luo; Yu-tong Song; Jia-jun Lei (Biochemical Genetics, 2019)

Nitrogen use-inefficient oilseed rape genotypes exhibit stronger growth potency during the vegetative growth stage - Xiao Guo; Huiying He; Rong An; Yuying Zhang; Rui Yang; Lanqin Cao; Xiaoming Wu; Biyun Chen; Hui Tian; Yajun Gao (Acta Physiologiae Plantarum, 2019)

Two new sesquineolignans from the seeds of Crataegus pinnatifida and their β -amyloid aggregation inhibitory activitiy - Rui Guo; Le Zhou; Peng Zhao; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2019)

Transcriptional regulation contributes more to Monascus pigments diversity in different strains than to DNA sequence variation - Xiaoyu Guo; Yao Li; Rui Zhang; Jiyuan Yu; Xinbao Ma; Mianhua Chen; Yurong Wang (World Journal of Microbiology and Biotechnology, 2019)

A new triterpene from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hong-Juan Song; Shuang Guo; Ying Wang; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2019)

Industrial environmental efficiency assessment for China’s western regions by using a SBM-based DEA - Si-Dai Guo; Hang Li; Rui Zhao; Xiao Zhou (Environmental Science and Pollution Research, 2019)

The origin and distribution of Ordovician Yingshan dolomite on the northern slope of Tazhong area in Tarim Basin - Zhao Jiahui; Zhao Rui; Wu Yasheng; Liu Tianjia; Cui Xuemin; Guo Kunzhang (Carbonates and Evaporites, 2019)

Lithological identification with probabilistic distribution by the modified compositional Kriging - Feilong Han; Hongbing Zhang; Qiang Guo; Jianwen Rui; Qiuyan Ji (Arabian Journal of Geosciences, 2019)

Metabolomics reveals the drought-tolerance mechanism in wild soybean (Glycine soja) - Xiaoxia Wang; Rui Guo; Mingxia Li; Yuan Liu; Mingli Zhao; Hui Fu; Xueying Liu; Shiyao Wang; Lianxuan Shi (Acta Physiologiae Plantarum, 2019)

Physiological and biochemical responses of Dunaliella salina exposed to acrylamide - Na Ling; Hong-Xiu Li; Hong-Shi Guo; Xiu-Ming Cao; Xiao-Rui Liu (Biologia, 2019)

Aspergilolide, a steroid lactone produced by an endophytic fungus Aspergillus sp . MBL1612 isolated from Paeonia ostii - Pei-Liang Zhang; Gang Wang; Feng-Qing Xu; Jin-Song Liu; Ju-Tao Wang; Rui Zhang; Hai-Tao Liu; Jiang-Miao Hu; Guo-Kai Wang; Pei-Yun Wu (Natural Product Research, 2019)

Uncommon Peptide Bond Cleavage of Glucagon from a Specific Vendor under near Neutral to Basic Conditions - Hong-Jian Zheng; Bin-Bin Shen; Jing Wang; Haibin Wang; Guo-Li Huo; Li-Rui Huang; Jian-Qing Gao; Wei-Jie Fang (Pharmaceutical Research, 2019)

Moon jellyfish aggregations observed by a scientific echo sounder and an underwater video camera and their relation to internal waves - Takashi Mano; Xinyu Guo; Naoki Fujii; Naoki Yoshie; Eisuke Tsutsumi; Rui Saito (Journal of Oceanography, 2019)

The severity of drought and precipitation prediction in the eastern fringe of the Tibetan Plateau - Yang Zhao; Xiangde Xu; Liufeng Liao; Yuhong Wang; Xiaoping Gu; Rui Qin; Yunyun Guo; Zhaoping Kang; Fang Wang; Min Wang (Theoretical and Applied Climatology, 2019)

Responses of nitrification and denitrification to nitrogen and phosphorus fertilization: does the intrinsic soil fertility matter? - Ying Wang; Hongfei Ji; Rui Wang; Shengli Guo (Plant and Soil, 2019)

ANKRD49 inhibits etoposide-induced intrinsic apoptosis of GC-1 cells by modulating NF-κB signaling - Xia Zhou; Wen-tao Wang; Jia Sun; Hong-yan Liu; Xin-yan Bai; Juan-juan Liu; Bao-feng Yu; Rui Guo; Hai-long Wang (Molecular and Cellular Biochemistry, 2019)

A new coumarin from Juglans mandshurica Maxim induce apoptosis in hepatocarcinoma cells - Li-Li Lou; Peng Zhao; Zhuo-Yang Cheng; Rui Guo; Guo-Dong Yao; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2019)

Depositional and diagenetic controls on the reservoir quality of Upper Triassic Chang-7 tight oil sandstones, southwestern Ordos basin, China - Ai Wang; Dakang Zhong; Haihua Zhu; Lele Guo; Zhuopei Li; Yangjinfeng Jiang; Xueqi Yang; Rui Xie; Xiaowei Zheng (Geosciences Journal, 2019)

A new method for evaluating the effectiveness of hydraulic fracturing in tight reservoirs - Fuping Feng; Rui Huang; Boyun Guo; Chi Ai; Chaoyang Hu; Yang Lei (Arabian Journal of Geosciences, 2019)

Dynamic Impedances of Offshore Rock-Socketed Monopiles - Rui He; Ji Ji; Jisheng Zhang; Wei Peng; Zufeng Sun; Zhen Guo (Journal of Marine Science and Engineering, 2019)
With the development of offshore wind energy in China, more and more offshore wind turbines are being constructed in rock-based sea areas. However, the large diameter and thin-walled steel rock-socketed monopiles are very scarce at present, and both the construction and design are very difficult. For the design, the dynamic safety during the whole lifetime of the wind turbine is difficult to guarantee. Dynamic safety of a turbine is mostly controlled by the dynamic impedances of the rock-socketed monopile, which are still not well understood. How to choose the appropriate impedances of the socketed monopiles so that the wind turbines will neither resonant nor be too conservative is the main problem. Based on a numerical model in this study, the accurate impedances are obtained for different frequencies of excitation, different soil and rock parameters, and different rock-socketed lengths. The dynamic stiffness of monopile increases, while the radiative damping decreases as rock-socketed depth increases. When the weathering degree of rock increases, the dynamic stiffness of the monopile decreases, while the radiative damping increases.

Highly Sensitive and Selective Fluorescent Probe for Detection of Fe3+ Based on Rhodamine Fluorophore - Yang Wang; Rui Guo; Xufeng Hou; Mengmeng Lei; Qihang Zhou; Zhihong Xu (Journal of Fluorescence, 2019)

Effects of organic-inorganic amendments on the cadmium fraction in soil and its accumulation in rice (Oryza sativa L.) - Bing Li; Lan Yang; Chang Quan Wang; Shun Qiang Zheng; Rui Xiao; Yong Guo (Environmental Science and Pollution Research, 2019)

Spatial distribution, source identification, and potential risk assessment of toxic contaminants in surface waters from Yulin, China - Jing Liu; Yongjun Liu; Aining Zhang; Yu Liu; Ying Zhu; Ming Guo; Rui Zhang (Environmental Monitoring and Assessment, 2019)

Diagentic features of illite in Upper Triassic Chang-7 tight oil sandstones, Ordos Basin - Ai Wang; Dakang Zhong; Haihua Zhu; Lele Guo; Yangjinfeng Jiang; Xueqi Yang; Rui Xie (Geosciences Journal, 2019)

Calpain-2 promotes MKP-1 expression protecting cardiomyocytes in both in vitro and in vivo mouse models of doxorubicin-induced cardiotoxicity - Dong Zheng; Zhaoliang Su; Yi Zhang; Rui Ni; Guo-Chang Fan; Jeffrey Robbins; Long-Sheng Song; Jianmin Li; Tianqing Peng (Archives of Toxicology, 2019)

Alkaloids from Juglans Mandshurica maxim induce distinctive cell death in hepatocellular carcinoma cells - Li-Li Lou; Zhuo-Yang Cheng; Rui Guo; Guo-Dong Yao; Shao-Jiang Song (Natural Product Research, 2019)

Genetic diversity and population structure of two endemic Cupressus (Cupressaceae) species on the Qinghai-Tibetan plateau - Yaru Fu; Shaoke Li; Qiqiang Guo; Weilie Zheng; Rui Yang; Huie Li (Journal of Genetics, 2019)

Numerical Simulations of Wave-Induced Soil Erosion in Silty Sand Seabeds - Zhen Guo; Wenjie Zhou; Congbo Zhu; Feng Yuan; Shengjie Rui (Journal of Marine Science and Engineering, 2019)
Silty sand is a kind of typical marine sediment that is widely distributed in the offshore areas of East China. It has been found that under continuous actions of wave pressure, a mass of fine particles will gradually rise up to the surface of silty sand seabeds, i.e., the phenomenon called wave-induced soil erosion. This is thought to be due to the seepage flow caused by the pore-pressure accumulation within the seabed. In this paper, a kind of three-phase soil model (soil skeleton, pore fluid, and fluidized soil particles) is established to simulate the process of wave-induced soil erosion. In the simulations, the analytical solution for wave-induced pore-pressure accumulation was used, and Darcy flow law, mass conservation, and generation equations were coupled. Then, the time characteristics of wave-induced soil erosion in the seabed were studied, especially for the effects of wave height, wave period, and critical concentration of fluidized particles. It can be concluded that the most significant soil erosion under wave actions appears at the shallow seabed. With the increases of wave height and critical concentration of fluidized particles, the soil erosion rate and erosion degree increase obviously, and there exists a particular wave period that will lead to the most severe and the fastest rate of soil erosion in the seabed.

Cytoprotective Mechanism of the Novel Gastric Peptide BPC157 in Gastrointestinal Tract and Cultured Enteric Neurons and Glial Cells - Xi-Yu Wang; Meihua Qu; Rui Duan; Dengping Shi; Ling Jin; Jinping Gao; Jackie D. Wood; Junhua Li; Guo-Du Wang (Neuroscience Bulletin, 2019)

Comparative detection of Karenia mikimotoi by exponential rolling circle amplification (E-RCA) and double-ligation E-RCA - Chunyun Zhang; Rui Sun; Yuanyuan Wang; Guofu Chen; Changlu Guo; Jin Zhou (Journal of Applied Phycology, 2019)

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

Integrated drought risk assessment of multi-hazard-affected bodies based on copulas in the Taoerhe Basin, China - Rui Wang; Jiquan Zhang; Enliang Guo; Si Alu; Danjun Li; Si Ha; Zhenhua Dong (Theoretical and Applied Climatology, 2019)

Comprehensive analysis of the whole coding and non-coding RNA transcriptome expression profiles and construction of the circRNA–lncRNA co-regulated ceRNA network in laryngeal squamous cell carcinoma - Rui Zhao; Feng-Qing Li; Lin-Li Tian; De-Si Shang; Yan Guo; Jia-Rui Zhang; Ming Liu (Functional & Integrative Genomics, 2019)